2019
DOI: 10.1177/0145482x19876463
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehension of STEM Graphics via a Multisensory Tablet Electronic Device by Students with Visual Impairments

Abstract: Introduction: The current work probes the effectiveness of multimodal touch screen tablet electronic devices in conveying science, technology, engineering, and mathematics graphics via vibrations and sounds to individuals who are visually impaired (i.e., blind or low vision) and compares it with similar graphics presented in an embossed format. Method: A volunteer sample of 22 participants who are visually impaired, selected from a summer camp and local schools for blind students, were recruited for the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Work with a prototype system, called a vibro-audio interface (VAI), based on a commercial tablet, has shown near identical accuracy between use of the VAI and hardcopy tactile stimuli for graph interpretation, pattern detection, and shape recognition [60]. In corroboration, studies by Gorlewicz and colleagues have demonstrated no significant differences in the interpretation of a variety of graphics including bar graphs, pie charts, tables, number lines, line graphs, and simple maps that were presented in embossed form and displayed multimodally on a touchscreen created by Vital [61,62]. Not only do these studies show the efficacy of this interface, but also that this multimodal platform can achieve similar performance to the gold standard of hardcopy graphics.…”
Section: Research Brief On Vibrotactile Touchscreen Displaysmentioning
confidence: 82%
“…Work with a prototype system, called a vibro-audio interface (VAI), based on a commercial tablet, has shown near identical accuracy between use of the VAI and hardcopy tactile stimuli for graph interpretation, pattern detection, and shape recognition [60]. In corroboration, studies by Gorlewicz and colleagues have demonstrated no significant differences in the interpretation of a variety of graphics including bar graphs, pie charts, tables, number lines, line graphs, and simple maps that were presented in embossed form and displayed multimodally on a touchscreen created by Vital [61,62]. Not only do these studies show the efficacy of this interface, but also that this multimodal platform can achieve similar performance to the gold standard of hardcopy graphics.…”
Section: Research Brief On Vibrotactile Touchscreen Displaysmentioning
confidence: 82%
“…Researchers have made several attempts to output tactile images by combining a haptic device with a braille display [13].…”
Section: Braille Padmentioning
confidence: 99%
“…Note that only two papers supported color information for photographs [35] and artwork [66]. Other information types include types of graph [53] and weather [24]. Five papers did not specify the information they provided.…”
Section: Information Typementioning
confidence: 99%